Secretion of acid Sphingomyelinase is affected by its polymorphic signal peptide - Rhein, Cosima; Reichel, Martin; Mühle, Christiane; Rotter, Andrea; Schwab, Sibylle; Kornhuber, Johannes (Cellular Physiology and Biochemistry, 2014)
Acid sphingomyelinase (ASM) catalyses the hydrolysis of sphingomyelin into ceramide, which acts as a lipid messenger that regulates important cellular functions. Deregulated ASM activity has been reported for different common diseases, but the mechanisms regulating ASM activity are still debated. ASM contains an exceptional signal peptide which is polymorphic due to a variable number of a hexanucleotide sequence that determines the length of the hydrophobic core. We investigated the impact of the signal peptide polymorphism on the regulation of ASM activity and secretion in vivo and in vitro.Subjects homozygous for the rare 4-repeat allele displayed significantly lower secreted ASM activity than subjects homozygous for the common 6-repeat allele. In vitro, overexpression of ASM variants encoded by 2, 8 or 9 repeats resulted in a significantly lowered ASM secretion rate. Treatment of ASM-overexpressing cells with tumour necrosis factor ? induced secretion of ASM, and the secretion rate was highest for the most common ASM variant encoding 6 repeats compared to other naturally occurring variants.We provide evidence that the polymorphic ASM signal peptide regulates ASM secretion. It might be an evolutionary mechanism to increase ASM secretion potential, whereas an increase in lysosomal ASM activity is limited due to deleterious cellular effects.
EVALuna2:23668